2014
DOI: 10.1007/s12010-014-1346-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Reactive Oxygen Species in Cytoplasmic Male Sterility of Rice by Marking Upmost Pulvinus Interval

Abstract: Reactive oxygen species (ROS) and malondialdehyde (MDA) in plant cell are thought to be important inducible factors of cell apoptosis if excessively accumulated in cells. To elucidate the metabolic mechanism of MDA production and scavenging in the cytoplasmic male-sterile (CMS) rice, CMS line and maintainer were employed for studying the relationship at different developmental stages by marking upmost pulvinus interval method of experiment. The results showed that the panicles and leaves of the CMS line had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…In addition, we detected continual increases in the MDA contents in the IAMSLs throughout anther development, where the MDA levels were higher than those in the maintainer line in the late uninucleate stage. Previous studies agree with our results, where they showed that excess ROS accumulated in the peak abortion stage and the activities of antioxidant enzymes were decreased significantly, thereby causing an imbalance in the generation and scavenging of ROS ( Jian et al, 2015 ). During the abortion peak (meiosis stage in pollen mother cells), another study found that the ROS contents increased greatly compared with the maintainer line and F1 hybrid, where the levels were much higher than normal ( Jiang et al, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we detected continual increases in the MDA contents in the IAMSLs throughout anther development, where the MDA levels were higher than those in the maintainer line in the late uninucleate stage. Previous studies agree with our results, where they showed that excess ROS accumulated in the peak abortion stage and the activities of antioxidant enzymes were decreased significantly, thereby causing an imbalance in the generation and scavenging of ROS ( Jian et al, 2015 ). During the abortion peak (meiosis stage in pollen mother cells), another study found that the ROS contents increased greatly compared with the maintainer line and F1 hybrid, where the levels were much higher than normal ( Jiang et al, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…A subtle ROS concentration is necessary for cell metabolism of various plant growth processes, such as root cell expansion and abiotic stress [27,84,85]. However, when there is an over-accumulation of ROS, which cannot be rapidly removed from cells, a ROS burst occurs and induces cell apoptosis and anther abortion [58,86]. MDA is an indicator of ROS in organisms and results from the enhancement of membrane lipid peroxidation, which damages the cell membrane and disturbs physiological metabolism inside the cell [87].…”
Section: Discussionmentioning
confidence: 99%
“…POD can prevent the excessive accumulation of MDA and ROS enzymes by decomposing H 2 O 2 into O 2 . Male sterility was reported to be due to dysfunction of the balance of POD content in floral organs [ 56 ]. POD is the last key enzyme in lignin synthesis, and down-regulated of Ciclev10001726m might ultimately influence lignin content in anther in ‘Wuzi Ougan’ before the tetrad stage in this research [ 57 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%